Dona, pobra, mare i fadrina contra l'autoritat moral. El procés inquisitorial d'Àgueda Guimerà (1804). - MOMPÓ NAVARRO, JACOB (Scripta, 2020)
In 1804, the Court of the Inquisition was living its last moments. Far from the great initial persecutions against Jews and Moors, the Holy Office seemed to languish, but certainly, although with less force than in past times, still was a formidable instrument of repression. In this context, Àgueda Guimerà, a single mother, and therefore criticized and mistreated, had to face a denunciation for slander by her confessor in which the suspicion of the crime of solicitation in the act of confession was floating in the air.